Smart System Kumbung Jamur Tiram dengan IoT dan Sensor DHT11-LDR - Rusito; Rahmawan, Andika Bagas (LogicLink, 2025)
Oyster mushroom cultivation requires stable environmental conditions, particularly in terms of temperature, humidity, and lighting. Traditionally, the management of mushroom houses has been carried out manually, which often leads to inefficiency and production failures. This study aims to design and implement a Smart System for oyster mushroom houses based on the Internet of Things (IoT) using DHT11 and LDR sensors. The research employed the Research and Development (R&D) method with six main stages, namely needs analysis, planning, initial product development, limited trials, product revision, and product testing. The system was designed using NodeMCU as the main controller, with the DHT11 sensor to measure temperature and humidity, and the LDR sensor to detect light intensity. Data are displayed through an LCD and transmitted in real time to an Android application. The design validation test obtained a score of 30, categorized as “Good,” while the limited user trial involving 12 respondents achieved an average score of 35.16, categorized as “Very Good (Valid).” The system automatically activates the fan when the temperature exceeds 28°C, turns on the water pump when humidity is low, and switches on the lamp when light intensity is insufficient. Therefore, this system can assist mushroom farmers in maintaining optimal environmental conditions in real time and automatically, which is expected to improve both the quality and productivity of oyster mushroom cultivation.